2020
DOI: 10.1021/acs.langmuir.0c01856
|View full text |Cite
|
Sign up to set email alerts
|

A New Antibacterial N-Halamine Coating Based on Polydopamine

Abstract: To prevent the formation of biofilm on material surface, the latter must have antibacterial properties. The aim of this study is to investigate the synthesis and the antibacterial effect of a new N-halamine coating based on polydopamine (PDA). The interests of this coating are multiple, notably the green process used to prepare it and the wide variety of organic or inorganic materials that can be functionalized. First the formation of the PDA coating by oxidative polymerization of dopamine in weak alkaline aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 54 publications
3
22
0
Order By: Relevance
“…The atomic ratio N/C is 0.065, whereas for PDA itself, it is higher, 0.125 (Table S1). The low N/C ratio indicates that the material is a composite of ERGO and PDA, in good agreement with the C 1s spectra (Figure S4).…”
Section: Resultssupporting
confidence: 80%
“…The atomic ratio N/C is 0.065, whereas for PDA itself, it is higher, 0.125 (Table S1). The low N/C ratio indicates that the material is a composite of ERGO and PDA, in good agreement with the C 1s spectra (Figure S4).…”
Section: Resultssupporting
confidence: 80%
“…As alternatives to these compounds, a class of antibacterial compounds, N-halamines, has attracted great interest in recent years [24][25][26]. These compounds contain nitrogenhalogen covalent bonds, which are formed by the halogenation of imide, amide or amine groups.…”
Section: Introductionmentioning
confidence: 99%
“…Cationic polymers are believed to impart antimicrobial activity by disrupting cell membrane functions mainly through an ionic exchange . Previous studies showed that the amine groups in PDA could be directly chlorinated and converted to N -halamine upon treatment with a dilute bleach solution to form an antimicrobial surface. , However, if N -halamine is completely consumed, the PDA surface will no longer have an antibacterial function. Therefore, we considered that the hybrid coatings that combine PDA and PEI will have the opportunity to form a dual biocidal surface with N -halamine (Figure ).…”
Section: Introductionmentioning
confidence: 99%